Relaxation of Static Photoelasticity in Lead Germanate Crystals - Demyanyshyn, N. M. (Ukrainian Journal of Physics, 2019)
The relaxation of static photoelasticity in lead germanate (Pb5Ge3O11) crystals has been studied. The anisotropy of relaxation amplitudes and their anomalies near the phase transition point were revealed. The photoelastic relaxations and peculiarities in their temperature behavior are explained as manifestations of the piezocaloric mechanism.